2019
DOI: 10.37544/0005-6650-2019-06-50
|View full text |Cite
|
Sign up to set email alerts
|

Untersuchungen zum Risswachstum in Verbunddübelleisten/Crack propagation investigations on composite dowels

Abstract: Zusammenfassung Im Verbundbrückenbau finden Verbund- dübelleisten aufgrund günstiger Tragfähigkeit und Ermüdungseigenschaften zunehmende Anwendung. Das Ermüdungskonzept der aktuellen allgemeinen Bauartgenehmigung der Verbunddübelleiste ist jedoch sehr konservativ, unter anderem weil es auf die Vermeidung der Ermüdungsinitiierung beispielsweise im Dübelzahn abzielt. Damit bleiben Umlagerungsmöglichkeiten der von Dübeln übertragenen Schubkräfte im Verbundträger ebenso unberücksichtigt wie die potenziell lange Ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 0 publications
1
13
0
1
Order By: Relevance
“…In contrast to the small part tests on a dowel, the shear forces transmitted by the composite dowels could not be directly controlled by the cylinder's force. Numerous preliminary investigations were carried out to select the upper and lower loads in the load cycles, which are described in [18]. The small part tests showed a pronounced crack initiation phase despite doweling, which is why the loads were initially selected somewhat higher for the first beam and then reduced from the measurable crack propagation, because the measured crack propagation rates indicated that the crack was growing too fast.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to the small part tests on a dowel, the shear forces transmitted by the composite dowels could not be directly controlled by the cylinder's force. Numerous preliminary investigations were carried out to select the upper and lower loads in the load cycles, which are described in [18]. The small part tests showed a pronounced crack initiation phase despite doweling, which is why the loads were initially selected somewhat higher for the first beam and then reduced from the measurable crack propagation, because the measured crack propagation rates indicated that the crack was growing too fast.…”
Section: Methodsmentioning
confidence: 99%
“…Within the framework of the research project, the crack propagation in composite dowels was initially investigated in small part tests with only one steel tooth [21]. The results of the small part tests were presented in [18]. On the basis of three fatigue tests on largeformat beams, the extent to which the findings of the small parts tests can be transferred to the steel tooth in the composite beam and which additional effects have to be taken into consideration is investigated.…”
Section: Test Set-up and Measurementmentioning
confidence: 99%
“…Von besonderem Interesse sind hierbei die Dehnungsmessstreifen (DMS) auf den Stahlzähnen der Verbunddübelleiste, da diese eine Aussage über das Versagen der Verbundfuge liefern können. Die Position der Messstreifen wurde ausgehend von den Erfahrungen vergangener Untersuchungen [25, 26] so gewählt, dass sie die Hotspot‐Spannungen der Stahlzähne messen können (Bild 8).…”
Section: Numerische Untersuchungenunclassified
“…Further investigations regarding rib shear connectors under static and cyclic loading were conducted in [9]. Investigation focusing on the steel fatigue of composite girders are included in [10] and [11]. The former publication included numerical and experimental investigation on rib shear connectors, while the…”
Section: State Of the Artmentioning
confidence: 99%